Photon indistinguishability measurements under pulsed and continuous excitation - Schofield,RC; Clear,C; Hoggarth,RA; Major,KD; McCutcheon,DPS; Clark,AS (arXiv, 2021)
The indistinguishability of successively generated photons from a singlequantum emitter is most commonly measured using two-photon interference at abeam splitter. Whilst for sources excited in the pulsed regime the measuredbunching of photons reflects the full wavepacket indistinguishability of theemitted photons, for continuous wave (cw) excitation the inevitable dependenceon detector timing resolution and driving strength obscures the underlyingphoton interference process. Here we derive a method to extract the photonindistinguishability from cw measurements by considering the relevantcorrelation functions. The equivalence of both methods is experimentallyverified through comparison of cw and pulsed excitation of an archetypal sourceof photons, a single molecule.